Mechanochemical in situ generated gas reactant for the solvent-free hydrogenation of porphyrins. Issue 2 (3rd April 2021) - Pineiro, Marta; Gomes, Carla; Peixoto, Mariana
ABSTRACT: The synthesis of chlorins was performed by hydrogenation of porphyrins using diimide generated and consumed under mechanical activation. The reaction conditions achievable under ball milling, absence of solvent and use of hydrazine hydrate as diimide source, allowed the hydrogenation of porphyrins with high conversion, high selectivity, and nearly ideal sustainability scores (atom economy of 97% and E-factor of 0.96). GRAPHICAL ABSTRACT: UF0001